Research Progress on Association of Dietary Fat and Fatty Acid Intake with Prognosis of Ovarian Cancer - WEI Yifan; GONG Tingting; GAO Song; WU Qijun (Zhongliu Fangzhi Yanjiu, 2023)
Ovarian cancer is characterized by insidious onset and poor prognosis, and among gynecological malignancies, its mortality rate ranks first, which poses a serious threat to women's health worldwide. In recent years, increasing evidence has suggested that modifiable lifestyle factors, particularly dietary factors, played important roles in the prognosis of ovarian cancer. As important nutrients, dietary fats and fatty acids can affect various vital physiological functions in human beings. However, the association of dietary fat and fatty acid intake with the prognosis of ovarian cancer remains unclear. Therefore, this review aims to analyze the existing epidemiological evidence between the two variables by searching the literature to provide dietary suggestions for ovarian cancer patients.